ANALISIS BUKU SEKOLAH ELEKTRONIK BAHASA INGGRIS SMP/MTs KURIKULUM 2013 WHEN ENGLISH RINGS THE BELL - , Laila Ulsi Qodriani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the quality of the English electronic textbook in curriculum 2013 for Junior High School grade VII âWhen English Rings the Bellâ through the analysis of the use of language and content, linguistic coverage, considerations are used seen from the principle of second language learning. The type of the research is descriptive qualitative study using content analysis method. The subjects were English electronic textbook for class VII written by Asep Gunawan, Yuli Rulani Khitmah, and Siti wachidah. This study analyzes the language, content, linguistic coverage, and considerations are used seen from the principle of second language learning. Data collection technique was done by using reading, sorting and noting. The data were analyzed textbook evaluation criteria by Wilga M. Rivers (1981) and the twelve principles of language learning by Douglas H. Brown. Based on the results, the nature of language and language use situations considered to be quite good, although it should be evaluated against the use of some vocabulary. Dialogue used in this textbook is the communication of daily life using short sentences and the reading text is interest the student. Cultural situation presented only focused on Indonesian culture without any knowledge of the native cultures. The earning about the differences in gender, race, religion given through pictures. Research on the linguistic coverage showed that there us no activity of pronunciation concern in form of written, no summary of the rules of grammar usage, and use of teaching aids such as tapes, recordings, video and others is not optimize. But the aspect of reading, vocabulary aspects, and aspects of writing is good because it is given to the various forms and is able to improve the language skills of the students on. In terms of relevance to second language learning principles are the integration of the various skills of language integration between skills such as listening and speaking skill integration, reading and writing skills integration, and speaking and writing skills integration. The use of visual aids in this book is also very helpful to understand the students learning the target language.